Spillover can limit accurate signal quantification in MPI - Ali Shakeri-Zadeh; Shreyas Kuddannaya; Adnan Bibic; Jeff W. M. Bulte (npj Imaging)
Abstract Accurate quantification of the magnetic particle imaging (MPI) signal in vivo remains a significant technical challenge. We assessed the “spillover effect”, defined as leakage of signal from adjacent areas within a region of interest, within a field of view containing multiple hot spots, a scenario frequently encountered in vivo after systemic administration of a magnetic tracer. Using custom-designed phantom and in vivo mouse studies we determined the impact of fiducial positioning, iron content, and the iron concentration ratios within those hot spots, as well as the suitability of four different MPI scan modes for accurate signal quantification. Adjustment of the specific “target-to-fiducial distance (TFD)” and “target-to-fiducial Fe concentration ratios (TFCR)” significantly reduced the spillover effect. It’s implementation to mitigate spillover effects will increase the accuracy of MPI for in vivo magnetic tracer quantification.